Filter Strength Selection Analysis In Direct Digital Radiography (DDR) on Phantom - Rasyid Rasyid; Siti Daryati; Panji Wibowo Nurcahyo (Jurnal Riset Kesehatan, 2014)
Filter Streng is one of software (build in) digital image processing in DDR, that’s have function to strecting of contras and to shaprp of result image with enhancment DDR image quality. In DDR avalaible 4 filter strength, aplicated for DDR image and for human anatomical likes bone, thotax and pelvis. This research is done by observational qualitative metode.Processing and analizing data is done from radiograph non filter and filtering. Resulting from respondent is done analizing and the hightest score is the best of image processing from contras strecting and image shapening. Every result grade in digital image processing by use software filter strengt fasility in X-rays DDR Medex to get image enhancment with watching contras deferent is more hight and more sharp, morethan to get noise is more hight. Image processing with using streng filter software in grade 3 is get result the best.